2000
DOI: 10.1159/000030109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Marker S-100 in Cerebrospinal Fluid from Subjects with Nonischemic Brain Pathologies

Abstract: In order to evaluate the S-100 concentration in cerebrospinal fluid from subjects with nonischemic brain damage, a total of 33 samples were analyzed: 11 from subjects in whom no organic disease could be found; 14 from patients with a diagnosis of lymphocytic or bacterial-fungal meningitis, and 8 from patients with acute lymphatic leukemia but no demonstrable signs of meningeal involvement. In all cases, the subjects considered had no previous history of melanoma or ischemic brain damage. The mean levels ± SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…A few studies on CNS infections have previously been conducted, studying meningitis (17 Á/19), encephalitis (18,20,21), fungal infections of the brain (19,22) and other aspects (23 Á/25). However, some of these studies are outdated and use older analysis kits, some deal only with CSF, some deal with other, less well documented, markers and 1 study involves animal models (22).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on CNS infections have previously been conducted, studying meningitis (17 Á/19), encephalitis (18,20,21), fungal infections of the brain (19,22) and other aspects (23 Á/25). However, some of these studies are outdated and use older analysis kits, some deal only with CSF, some deal with other, less well documented, markers and 1 study involves animal models (22).…”
Section: Discussionmentioning
confidence: 99%
“…In bacterial-fungal or lymphocytic menigitis, an increase of S100 CSF levels has been reported (Infante et al, 2000). In an earlier study, Sindic and colleagues (1982) reported increased S100 CSF levels in patients with viral and to a lesser extent with bacterial meningitis.…”
Section: Inflammation Infectionmentioning
confidence: 94%
“…Lamers and colleagues (1995) failed to find any differences concerning S100 CSF concentrations in meningitis. The comparability of these studies is impaired because all three studies used different assays with a variety of lower detection limits (Sindic et al (1982): 2,500 ng/L, Lamers et al (1995): 500 ng/L, Infante et al (2000): 200 ng/L). In neuroborreliosis, S100 CSF concentrations did not alter with clinical improvement (Dotevall et al, 1999).…”
Section: Inflammation Infectionmentioning
confidence: 99%
“…Several previous studies have investigated the role of protein S-100B and/or NSE in meningitis, neuroborreliosis and lymphatic leukaemia (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%